Ways of enhancing joyful teaching and learning in a graduate class of Nepal - Parbati Dhungana (Educational Journal of Living Theories)
Adapting a Living Educational Theory Research methodology, I discuss how my teaching, my learning, and my research contributed to the enhancement of joyful teaching and learning in a university classroom. I share my own living-educationaltheory that influenced me, my colleagues, students, and the university culture. Inspired by Bhagavad Gita and using a participatory action research design and dialogue method, I collected and analyzed data from reflective journals, presentations, assignments, and blog writing. In this paper, I present a cluster of five context-responsive approaches (voluntary participation, valuing a sense of wonderment, respecting interdependence, enhancing the Culture of Inquiry, and adapting aesthetic inquiry) as I answer the question: How can I enhance joyful teaching and learning in my graduate classes? Finally, I share three prerequisites and a challenge of promoting joyful teaching and learning in higher educational contexts.